PGSD Students' Learning Interest in Learning Using the Learning Management System (LMS) - Muamila; Azizah; Zulnuraini (Tadulako Social Science and Humaniora Journal, 2021)
Online learning for educators is a change that must be made by lecturers to continue teaching students. Online learning aims to improve the quality of education. The first research problem is the application of the Learning Management System at Tadulako University, the second is how the learning interest of PGSD students in learning using LMS. The purpose of the first study was to describe the application of the LMS in learning in the PGSD study program at Tadulako University, the second was to describe the learning interest of PGSD students in learning using LMS. Methods The research method used is qualitative. Then, the author understands and explores the phenomenon to see the effectiveness of the application. To see the effectiveness of the application, the data that has been collected is described in words by the author, who draws conclusions from the problem. the problem. The results of the research from the questionnaire on average students are happy with the learning system using LMS. The conclusion of this research is Interest in students using LMS, namely, students are very happy with the existence of an online online-based learning system through the LMS website, students can access materials and assignments given by lecturers, students are also used to access materials and assignments given by lecturers, students are also accustomed to utilizing technology in learning. utilize technology in learning.